2020
DOI: 10.1186/s12884-020-02976-y
|View full text |Cite
|
Sign up to set email alerts
|

Andersen’s model on determining the factors associated with antenatal care services in Nepal: an evidence-based analysis of Nepal demographic and health survey 2016

Abstract: Background: With the formulation of the National Safe Motherhood Policy in 1998, safe motherhood has forever been a priority program in Nepal. Under the safe motherhood program, every woman is provided with essential maternal health care services until now through the four-tire district health care system. There is a considerable increase in the utilization of antenatal care (ANC) by a skilled health provider from 2011 to 2016, 58 to 84%, respectively. However, inequality, exclusion, and under-utilization in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
(28 reference statements)
8
15
1
3
Order By: Relevance
“…The odds of not attending antenatal care service were reduced when educational status is increased. The finding was supported by previous researches in Western Ethiopia [ 62 ], Ethiopia [ 56 ], rural Ethiopia [ 51 ], Kenya [ 90 ], Guinea [ 55 , 91 ], Afghanistan [ 64 ], Angola [ 54 ], East African countries [ 60 ], India [ 92 , 93 ], Ghana [ 94 ], Nepal [ 95 ], Nigeria [ 96 ]. Educated women might empowered to get services [ 97 102 ], education make women to have decision making [ 103 , 104 ].…”
Section: Discussionsupporting
confidence: 82%
“…The odds of not attending antenatal care service were reduced when educational status is increased. The finding was supported by previous researches in Western Ethiopia [ 62 ], Ethiopia [ 56 ], rural Ethiopia [ 51 ], Kenya [ 90 ], Guinea [ 55 , 91 ], Afghanistan [ 64 ], Angola [ 54 ], East African countries [ 60 ], India [ 92 , 93 ], Ghana [ 94 ], Nepal [ 95 ], Nigeria [ 96 ]. Educated women might empowered to get services [ 97 102 ], education make women to have decision making [ 103 , 104 ].…”
Section: Discussionsupporting
confidence: 82%
“…The odds of not attending antenatal care service were reduced when educational status is increased. The nding was supported by previous researches in Western Ethiopia (62), Ethiopia(56), rural Ethiopia(51), Kenya (90), Guinea (55,91), Afghanistan (64), Angola (54), East African countries (60), India (92,93), Ghana (94), Nepal (95), Nigeria (96). Educated women might empowered to get services (97)(98)(99)(100)(101)(102), education make women to have decision making (103,104).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, Tesfaye et al (2018) further identified education as a predisposing IJSE 48,1 factor to ANC use. The study by Tesfaye et al (2018) and Zhang et al (2019) also identified wealth index, income, travel cost and husband's attitude towards ANC as significant enabling factors, whereas need factors were generated from functional and health problems that create the need for health-care services (Kim and Lee, 2016;Neupane et al, 2020).…”
Section: Methodology and Data Source Theoretical Frameworkmentioning
confidence: 99%